2018
DOI: 10.1021/acs.est.8b03287
|View full text |Cite
|
Sign up to set email alerts
|

Using High-Resolution Mass Spectrometry to Identify Organic Contaminants Linked to Urban Stormwater Mortality Syndrome in Coho Salmon

Abstract: Urban stormwater is a major threat to ecological health, causing a range of adverse, mostly sublethal effects. In western North America, urban runoff is acutely lethal to adult coho salmon ( Oncorhynchus kisutch) that spawn each fall in freshwater creeks. Although the mortality syndrome is correlated to urbanization and attributed to road runoff contaminant(s), the causal agent(s) remain unknown. We applied high-resolution mass spectrometry to isolate a coho mortality chemical signature: a list of nontarget an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
204
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(221 citation statements)
references
References 64 publications
(118 reference statements)
10
204
1
1
Order By: Relevance
“…Other researchers studying the water chemistry and biology have shown that this hyporheic restoration has also been effective at significantly reducing concentrations of incoming pollutants [29], and at enhancing both hyporheic microbial heterotrophic production and macroinvertebrate taxa diversity and richness [37]. Table A2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers studying the water chemistry and biology have shown that this hyporheic restoration has also been effective at significantly reducing concentrations of incoming pollutants [29], and at enhancing both hyporheic microbial heterotrophic production and macroinvertebrate taxa diversity and richness [37]. Table A2.…”
Section: Discussionmentioning
confidence: 99%
“…Using mass spectroscopy, Peter et al [30] found significant reductions in the number and concentration of organic chemicals, some of which are potentially associated with coho mortality (as identified in [29]) both under both base flow and stormflow conditions through plunge-pool No. 4 at the Kingfisher site.…”
Section: Relation To Other Studies and Observationsmentioning
confidence: 99%
“…123,124 Exposure of healthy coho spawners to untreated highway runoff collected during storm events reproduced the mortality syndrome indicating that coho salmon are vulnerable to one or more chemicals present in runoff. 124,123 Using high-resolution mass spectrometry (HRMS), Peter et al 125 developed a chemical signature for the coho mortality by isolating HRMS features (i.e., exact mass-retention time pairs) that co-occurred in road runoff and field samples that caused symptomatic coho. This "coho mortality signature" was then compared to chemical signatures of several motorvehicle fluids and tire wear particle leachate.…”
Section: Toxicological Relevance Of Hydrophilic Trocs In Urban Stormwmentioning
confidence: 99%
“…This "coho mortality signature" was then compared to chemical signatures of several motorvehicle fluids and tire wear particle leachate. 125 The chemical signature of tire wear particle leachate displayed most similarity to waters that caused coho mortality. 125 Prominent chemicals identified in the coho mortality signature were octylphenol ethoxylates, glycols, bicyclic amines, and (methoxymethyl)melamine compounds.…”
Section: Toxicological Relevance Of Hydrophilic Trocs In Urban Stormwmentioning
confidence: 99%
“…Subsequent analyses that incorporated water samples from urban streams where spawning Coho Salmon consistently die prematurely in response to toxic stormwater (Scholz et al 2011) has narrowed the list of causal toxic agents to fewer than 100 chemicals (Peter et al 2018). Moreover, the HRMS approach revealed the presence of a family of (methoxymethyl) melamine compounds in urban waterways, the first such detections in North American surface waters (Peter et al 2018). These contaminants were subsequently linked to urban stormwater-related mortality syndrome in Coho Salmon, until then known to be the causing agent.…”
Section: Progress In Analytical Chemistry Allows For More Comprehensimentioning
confidence: 99%